Megamitochondria formation in hepatocytes of patient with chronic hepatitis C – a case report - Wieczorek, Anna; Stępień, Piotr M.; Zarębska-Michaluk, Dorota; Kryczka, Wiesław; Pabjan, Paweł; Król, Teodora (Clinical and Experimental Hepatology, 2017)
Although chronic hepatitis C virus (HCV) infection affect 185 million people world-wide, pathomechanism of liver damage is still unclear. Electron microscopy can reveal liver injury in very early stage and help understanding the mechanisms that is crucial in the pathogenesis of chronic hepatitis C. We present the morphological changes in the liver of HCV infected 24-year-old female patient, using light and transmission electron microscopy. Examination by TEM revealed wide range of specific subcellular abnormalities in hepatocellular ultrastructure. The most common observed changes were ring-shaped nuclei with intranuclear inclusion, megamitochondria, and “membranous web” structures – the hallmark of RNA-viruses infection.